FAKTOR FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN MANUFAKTUR - Brian Pramaharjan; Nur Cahyonowati (Diponegoro Journal of Accounting, 2015)
The aim of this study is to examine the influence of profitability, solvability, the size of audit committee , the size of the company, and the size of public accounting firm on audit report lag. The population in this study are all companies in manufacture industries that listed on the Indonesian Stock Exchange, selected using purposive sampling during 2011 until 2014. The number of samples used in the study are 100 companies. The test result shows that profitability, the size of the company, and the size of public accounting firm have influence on audit report lag, while on the other hand solvability and the size of audit committee have no influence on audit report lag.